PENINGKATAN KEMAMPUAN MENULIS DESKRIPSI MELALUI MODEL CONCEPT SENTENCE BERBANTUAN MEDIA FLASHCARD PADA SISWA KELAS IV SD NEGERI UNGGULAN BONTOMANAI KABUPATEN GOWA - Asniar; Andi Adam; Desy Ayu Andhira (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the improvement of descriptive writing skills through the Concept Sentence model assisted by flashcards in fourth-grade students of SD Negeri Unggulan Bontomanai, Gowa Regency. This study is a Class Action Research (CAR) consisting of two cycles, each with three meetings. The research procedures included planning, implementation, observation, and reflection. The subjects were 28 fourth-grade students of SD Negeri Unggulan Bontomanai, Gowa Regency. The collected data were analyzed using quantitative and qualitative analysis. The results showed that in the first cycle, only 13 of the 28 students, or 46%, individually completed the writing, meeting the minimum passing grade (KKM), or falling into the very low category. The classical criteria were not met, as the average score was 66%. However, in Cycle II, 28 students, or 100%, met the Minimum Competency (KKM) and the classical criteria were met, with an average score of 94%, which is in the very high category. Based on the research results above, it can be concluded that the descriptive writing skills of fourth-grade students at Unggulan Bontomanai Elementary School, Gowa Regency, have improved through the application of the Concept Sentence model with the aid of flashcards.